2019
DOI: 10.1088/1361-6455/ab46f9
|View full text |Cite
|
Sign up to set email alerts
|

Tunneling of persistent currents in coupled ring-shaped Bose–Einstein condensates

Abstract: Considerable progress in experimental studies of atomic gases in a toroidal geometry opens up novel prospects for the investigation of fundamental properties of superfluid states and creation of new configurations for atomtronic circuits. In particular, a setting with Bose-Einstein condensates loaded in a dual-ring trap suggests a possibility to consider the dynamics of tunneling between condensates with different angular momenta. Accordingly, we address the tunneling in a pair of coaxial three-dimensional (3D… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 51 publications
0
17
0
Order By: Relevance
“…Note that the Josephson oscillations do not change the chemical potential in Eq. (35), which is borrowed from the respective single-layered solutions, that contain the factor of exp (−iμt ).…”
Section: A Exact Solutions For Josephson Oscillations In the Linear mentioning
confidence: 99%
See 2 more Smart Citations
“…Note that the Josephson oscillations do not change the chemical potential in Eq. (35), which is borrowed from the respective single-layered solutions, that contain the factor of exp (−iμt ).…”
Section: A Exact Solutions For Josephson Oscillations In the Linear mentioning
confidence: 99%
“…This regime, which is again possible solely in the nonlinear system, cf. exact solution (35) obtained in the linear limit (which actually corresponds to the system strongly dominated by the intercore coupling), takes place if the strength of the Josephson interaction exceeds a certain threshold value, κ > κ thr . The dependence of the threshold on the total norm in one layer, N, is shown in Fig.…”
Section: Fig 3 the Same As Inmentioning
confidence: 99%
See 1 more Smart Citation
“…Weakly coupled condensates have been proposed as basic building blocks for quantum technologies [38][39][40][41]. In particular, the dynamics of BECs in tunnel-coupled ring potentials have been thoroughly explored in a variety of geometries such as stacked rings with [42,43] or without lattices [44][45][46][47][48], concentric rings [49,50], or coplanar rings [51,52].…”
Section: Introductionmentioning
confidence: 99%
“…Gaining control over the tunnelling of persistent currents in a double-ring geometry would closer emulate the geometry of the original theoretical scheme. Recently, several proposals for two parallel/stacked rings have shown that the winding number can tunnel between rings due to the creation of fluxons at their boundary [43], and at the single-particle level persistent current tunnelling has been predicted between arrays of adjacent rings and in similar configurations [44,45,46,47]. The aim of this work is to explore the full two-dimensional (2D) formation dynamics of spontaneous supercurrents in such a side-by-side geometry, and demonstrate the resulting (perhaps somewhat counter-intuitive) independence of the two connected rings, despite their density overlap and coupled dynamics.…”
Section: Introductionmentioning
confidence: 99%